Exploring the genetic variability for higher water productivity in wheat crop under moisture stress conditions - Meena, Raj Pal; Kumar, Neeraj; Gupta, Vikas; Verma, Ajay; Tripathi, Subhash Chandra; Kumar, Priya Ranjan; Singh, Gyanendra Pratap (Journal of Cereal Research, 2022)
Wheat is the flagship and staple food crop in India. Cultivation of wheat taking place under assured irrigation facility in India. One of the biggest difficulties faced by wheat farmers in all regions is depletion of ground water resources at an alarming rate. This study was conducted to test the hypothesis that variability with respect to water use efficiency exists in wheat genotypes and the use of higher water use efficient genotypes reduced the amount of irrigation water for harvesting the desirable level of yield. The field experiment was carried out in split plot design during rabi season of 2020-21 under two different moisture levels. Genotype DBW 110 was top ranked for WUE (1.28 kg/M3 & 1.71 kg/M3) at IARI Gauria Karma. Whereas at Karnal centre, genotype 40 ESWYT 33 ranked first with WUE of 2.42 and 3.04 kg/M3 under 80 and 60 % of ET respectively. Identification and deployment of wheat genotypes having higher water use efficiency could be the water saving technology in the water scarce scenario